FINANCING HEALTHCARE SYSTEM IN POLAND: EXPERIENCE FOR UKRAINE - Gaidash D.S. (Pressing Problems of Public Administration, 2015)
The article covers performance and components of the funding facility for the healthcare system in Poland. The author also suggests ways to transform and improve the performance of healthcare in Ukraine.